2008
DOI: 10.2134/jeq2007.0392
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Losses in Leaching and Surface Runoff from Manure‐Amended Agricultural Land

Abstract: A 3-yr field study quantified leaching and runoff losses of antibiotics from land application of liquid hog (chlortetracycline and tylosin) and solid beef (chlortetracycline, monensin, and tylosin) manures under chisel plowing and no-tillage systems. The study was conducted in southwestern Wisconsin, a karst area with steep, shallow, macroporous soils. Relative mass losses of chlortetracycline, monensin, and tylosin were <5% of the total amount applied with manure. Chlortetracycline was only detected in runoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(115 citation statements)
references
References 40 publications
10
103
1
1
Order By: Relevance
“…Only a fraction of antibiotics fed to swine are metabolized by them, the nonmetabolized antibiotics or residues may remain unchanged through the animal digestion system and they are excreted in animal waste (Gustafson and Bowen, 1997;Onan and LaPara, 2003). Up to 90% of fed antibiotics have been found to be released with urine and feces (Chander et al, 2006;Dolliver and Gupta, 2008). Table 1 lists all antimicrobial agents used in swine feeds.…”
Section: Sub-therapeutic Usage Of Antibiotics In Swine Production Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a fraction of antibiotics fed to swine are metabolized by them, the nonmetabolized antibiotics or residues may remain unchanged through the animal digestion system and they are excreted in animal waste (Gustafson and Bowen, 1997;Onan and LaPara, 2003). Up to 90% of fed antibiotics have been found to be released with urine and feces (Chander et al, 2006;Dolliver and Gupta, 2008). Table 1 lists all antimicrobial agents used in swine feeds.…”
Section: Sub-therapeutic Usage Of Antibiotics In Swine Production Andmentioning
confidence: 99%
“…Previous researches have determined that tylosin can enter the environment in significant concentrations and land-applied tylosin in manure can sorb to the soil or move to surface and groundwater (Allaire et al, 2006;Clay et al, 2005;Dolliver and Gupta, 2008;Kolpin et al, 2002;Kolz et al, 2005;Loke et al, 2002). Tylosin has high potential to transport with sediment during runoff events due to its sorption characteristics to manure and soil particles (Davis et al, 2006;Loke et al, 2002).…”
Section: Tylosin Use In Swine Production and Persistence Of Tylosin Rmentioning
confidence: 99%
“…Prior studies have identified elevated levels of antibiotics, antibioticresistant bacteria and antibiotic resistance genes in ground and surface water surrounding confined animal feeding operations (Campagnolo et al, 2002;Chee-Sanford et al, 2009;Heuer et al, 2011). The potential for antibiotics, antibiotic-resistant bacteria and antibiotic-resistance genes leaching into the environment is becoming of greater concern, with approximately 9.2 million hectares of farmland receiving manure annually (Dolliver and Gupta, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Chinese livestock farms, most of wastewater and manure are directly or indirectly discharged into surface water or applied onto agricultural land, resulting in the contamination of antibiotics in aquatic and terrestrial environments. Antibiotics associated with livestock manure and wastewater application onto land can also enter surface water via run off, or leach into groundwater (Davis et al, 2006;Dolliver and Gupta, 2008). So far, antibiotic residues have been reported in the surrounding environments of animal farms, with the concentrations from not detected to 2683 μg/kg in soil (Hu et al, 2010;Li et al, 2011), from 2 ng/L to 6800 ng/L in surface water (Christian et al, 2003;Matsui et al, 2008), and from 1.4 to 1400 ng/L in groundwater (Batt et al, 2006;Campagnolo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%